Acylphloroglucinols as kinase inhibitors from Sargassum nigrifoloides. Issue 7 (3rd July 2019) - Jiang, Cheng-Shi; Wang, Yin-Yin; Song, Jin-Tong; Yu, Jin-Hai
Abstract: Three new acylphloroglucinols (1 –3 ) and four known biosynthetically related analogs (4 –7 ) were isolated from the ethanol extract of a brown alga Sargassum nigrifoloides . Structures for1 –7 were characterized via detailed spectroscopic analyses especially 2D NMR data. Screening of these compounds in Alzheimer's diseases-related bioassays revealed moderate inhibitory activities against two therapeutically important kinases, CDK5 and GSK3β. A preliminary structure–activity relationship was also discussed. Abstract :